2013
DOI: 10.1016/j.bbalip.2012.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Lysophosphatidic acid (LPA) and its receptors: Role in airway inflammation and remodeling

Abstract: Lysophosphatidic acid (LPA), a simple bioactive phospholipid, is present in biological fluids such as plasma and bronchoalveolar lavage (BAL). It appears to have both pro- and anti-inflammatory roles in inflammatory lung diseases. Exogenous LPA promotes inflammatory responses by regulating the expression of chemokines, cytokines, and cytokine receptors in lung epithelial cells. In addition to the modulation of inflammatory responses, LPA regulates cytoskeleton rearrangement and confers protection against lung … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
98
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(101 citation statements)
references
References 61 publications
(136 reference statements)
3
98
0
Order By: Relevance
“…At the dose used in this study, the C max of LPC in the sera of the mice was 2-to 3-fold higher than the 10 to 30 M required to induce the chemotaxis of immune cells (24,26), and this treatment did not induce any apparent toxic effects in the mice. In the peritoneal sepsis model, we observed that 60% of the LPC-treated mice were negative for bacteremia and that 40% of the LPC-treated mice survived.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…At the dose used in this study, the C max of LPC in the sera of the mice was 2-to 3-fold higher than the 10 to 30 M required to induce the chemotaxis of immune cells (24,26), and this treatment did not induce any apparent toxic effects in the mice. In the peritoneal sepsis model, we observed that 60% of the LPC-treated mice were negative for bacteremia and that 40% of the LPC-treated mice survived.…”
Section: Discussionmentioning
confidence: 98%
“…The decreased LPC concentration may reflect its enhanced and rapid conversion to lysophosphatidic acid (LPA) by a plasmatic lysophospholipase D (23). LPA is known to induce a multitude of cellular responses, including LPA-driven effects on proinflammatory cytokine production (24). Clinically, it was reported that plasma LPC was significantly decreased in septic patients (25,26), and patients with unfavorable sepsis outcomes had significantly lower plasma LPC-phosphorylcholine levels than patients who survived a septic episode (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…It can be made intracellularly and also in the extracellular compartment, such as the plasma ( 16 ). It has a relatively short half-life of less than a few minutes due to catabolism by lipid phosphate phosphatases ( 19 ). Most extracellular LPA is bound to albumin, which, like S1P, may inhibit its cell signaling activity by reducing its bioavailability.…”
mentioning
confidence: 99%
“…In general, LPA containing unsaturated fatty acids are more potent in their biological activity, which is consistent with the result found in this study showing that LPA 18:0 was relatively inert. Intracellular LPA can also generate cell signaling events by the stimulation of nuclear membrane receptors ( 19 ). For example, intracellular LPA can activate the nuclear receptor PPAR-γ ( 16 ), which is a well-known transcription factor involved in lipid metabolism and atherosclerosis.…”
mentioning
confidence: 99%
“…LPA is involved in many pathological processes, including neurological disorders, cardiovascular disease, inflammation, lung and renal fibrosis, and cancer (Choi et al 2010, Pyne et al 2013). Experimental and clinical evidence strongly suggests that LPA is involved in lung pathology and disease, including airway repair and remodeling, inflammation, and fibrosis via LPA receptor signaling (Oikonomou et al 2012, Shea & Tager 2012, Tager et al 2008, Toews et al 2002, Zhao & Natarajan 2013. LPAR1 or endothelial differentiation gene (EDG) family member 2 (EDG2), is the first identified LPA receptor with high affinity to LPA.…”
Section: Introductionmentioning
confidence: 99%